Coping mechanisms of parents of pediatric cancer patients - Dizon, Wilman G.; Labarda, Maria Genevieve C.; Lumabao, Gina Angela B.; Pagtakhan, Ronivin G.; Reyes, Maureen S.; Godofredo, Sorra Jr., S.; Villazor, Erika Bianca S.
This study carried the main problem identifying most helpful coping mechanisms used by parents of pediatric patients having cancer in a tertiary hospital. A total number of 70 parents of pediatric cancer patients were included in the study qualified in the set of sample criteria. This included men and women who/whose (1) were a parent of a pediatric patient medically diagnosed with cancer (2) child must be admitted in the pediatric units of the tertiary hospital or having follow-up consultations to the out-patient department (OPD) of the hospital (3) were presently living with the child (4) were willing to participate in a study through informed consent. All qualified subjects in the pediatric ward and the OPD were included in the sample. The data were gathered using a two-level questionnaire as a research tool. The first-level focused on the socio-demographic variables of the parents and the information regarding the medical status of the child. The second-level was the Coping Health Inventory of Parents (CHIP), a standard instrument used to identify parental coping mechanisms. From the data analysis and interpretation obtained, the investigators concluded that “Maintaining family integration, cooperation, and an optimistic definition of the situation (CHIP A)” is the most helpful coping mechanism used by parents of pediatric cancer patients. Moreover, there is a significant relationship between the use of coping mechanisms and the variables that include the level of income, and the degree of satisfaction from the non-family member support system.